Series Active Variable Geometry Suspension application to comfort enhancement. (February 2017) - Arana, Carlos; Evangelou, Simos A.; Dini, Daniele
Abstract: This paper explores the potential of the Series Active Variable Geometry Suspension (SAVGS) for comfort and road holding enhancement. The SAVGS concept introduces significant nonlinearities associated with the rotation of the mechanical link that connects the chassis to the spring-damper unit. Although conventional linearization procedures implemented in multi-body software packages can deal with this configuration, they produce linear models of reduced applicability. To overcome this limitation, an alternative linearization approach based on energy conservation principles is proposed and successfully applied to one corner of the car, thus enabling the use of linear robust control techniques. An H ∞ controller is synthesized for this simplified quarter-car linear model and tuned based on the singular value decomposition of the system's transfer matrix. The proposed control is thoroughly tested with one-corner and full-vehicle nonlinear multi-body models. In the SAVGS setup, the actuator appears in series with the passive spring-damper and therefore it would typically be categorized as a low bandwidth or slow active suspension. However, results presented in this paper for an SAVGS-retrofitted Grand Tourer show that this technology has the potential to also improve the high frequency suspension functions such as comfort and road holding. Abstract : Highlights: Mechatronic suspension control for comfort and road holding enhancement proposed. Control synthesis relies on linear dynamics by geometric nonlinearity cancellation. H ∞ control framework offers robustness against noise and disturbances. Performance improves compared to passive suspension for operation on uneven road.